Membongkar Fungsi Makanan Terkait Ritual Keagamaan dalam Sanggring Gumeno: Suatu Analisis Antropologi Kuliner - Mega Rizqianah; Aliffiati .; A.A. Ayu Murniasih (Department of Anthropology Udayana University, 2021)
Food and culture are closely related. Food is not only about eating processed food but has complex symbolic values. Sanggring Gumeno is a culinary tradition related to religion which is held every night of 23 Ramadan in Gumeno Gresik Village, East Java. Sanggring Gumeno is a food cooking activity called chicken compote to be served when breaking fast together. Chicken compote is believed to be a medicine, because it refers to the illness experienced by Sunan Dalem (Sunan Giri's first son) when broadcasting Islam in Java, especially in Gumeno Village. In addition, chicken compote contains the complexity of symbolic values in it. The theory used in this research is the food function theory from Foster and Anderson. This theory is useful for investigating and unraveling the symbolic values of Sanggring Gumeno. Foster and Anderson suggest that symbolically food can take the form of at least four expressions, namely (a) social ties, (b) group solidarity, (c) food and mental tension, and (d) food symbolism in language. The method used in this study is a qualitative method with observation and interview data collection techniques. Data analysis used interpretive descriptive analysis. The results showed that Sanggring Gumeno symbolically represented the religious attitude of the religious community. Through Sanggring Gumeno, the people of Gresik in general and the people of Gumeno Village in particular take advantage of this historic moment to tie ties (ukhuwah islamiyah). Sanggring's function related to religious rituals is found in the existence of social ties (family gatherings), group solidarity (mutual cooperation), and mental tension (feelings of belonging).